Effect of GGBS Slag on Setting Time and Compressive Strength of One-Part Geopolymer Binders - Sani Haruna; Bashar S. Mohammed; M. M.A Wahab (Journal of Infrastructure & Facility Asset Management, 2020)
This paper investigated the influence of ground granulated blast furnace slag (GGBS) on the setting time and compressive strength of one-part geopolymer binders (OPGB). Powdered sodium metasilicate activator was utilized in the range of 8 – 16% by weight of the total binder. Central composite design method was used in designing the mixtures. Experimental investigation revealed that both the initial and final setting time of the OPGB decreased drastically with the increase in the GGBS and the activator content. The inclusion of GGBS in the binder influences the setting time of the binders thereby resulting in quick setting time. The variance analysis of the established models demonstrated that the setting and compressive strength models could be predicted using quadratic models with high R2 coefficient. Optimizations results revealed that the optimum mixture can be obtained by substituting 95.8 % fly ash with GGBS and 13.4 % solid activator.